A micro-economic approach to geographic market definition on local retail markets: Demand side considerations - Walter Beckert (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
This paper formalizes an empirically implementable framework for the definition of local antitrust markets in retail markets. This framework rests on a demand model that captures the trade-off between distance and pecuniary cost across alternative shopping destinations within local markets. The paper develops, and presents estimation results for, an empirical demand model at the store level for groceries in the UK.
Keywords: L11; L13; L41; L81; C35; C73; 330; Geographic antitrust market definition; discrete choice; Einzelhandel; Region; Relevanter Markt; Einkaufsstättenwahl; Konzentrationspolitik; Großbritannien